2022
DOI: 10.1177/11782218221132397
|View full text |Cite
|
Sign up to set email alerts
|

Effects of VHA Policy Directive 1163 on Acceptance and Employment Rates for Veterans with Substance Use Disorders Referred to VHA Vocational Rehabilitation

Abstract: Introduction: Research has shown that Veterans with Substance/Alcohol Use Disorders (SUDs/AUDs) are at a greater risk for employment-related issues (eg, lower labor force participation rates), and interventions such as Vocational Rehabilitation (VR) have been used as a tool to reduce employment obtainment and maintenance. The purpose of the current study was to evaluate acceptance rates and employment rates at closure for Veterans with SUDs/AUDs prior to the implementation of VHA Policy Directive 1163 (mandate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…VR is a method of assisting veterans to obtain the skills and tools needed to successfully secure and maintain competitive employment. A primary focus is on removing employment-related barriers for veterans that have difficulty obtaining or maintaining employment (18,19). VHA VR programs are expected to adhere to VHA Policy Directive 1163.02, which was released on August 19, 2019.…”
Section: Vha Vocational Rehabilitationmentioning
confidence: 99%
See 3 more Smart Citations
“…VR is a method of assisting veterans to obtain the skills and tools needed to successfully secure and maintain competitive employment. A primary focus is on removing employment-related barriers for veterans that have difficulty obtaining or maintaining employment (18,19). VHA VR programs are expected to adhere to VHA Policy Directive 1163.02, which was released on August 19, 2019.…”
Section: Vha Vocational Rehabilitationmentioning
confidence: 99%
“…VHA VR programs are expected to adhere to VHA Policy Directive 1163.02, which was released on August 19, 2019. Prior research has shown that implementation of this policy did not impact program enrollment rates for veterans with SUDs, but veterans with AUDs were less likely to be enrolled prior to the implementation of VHA Policy Directive 1163 (18). This policy explicitly states the following: "no discriminatory practices are acceptable for Veterans with SUD or AUDs "regardless of duration of sobriety, routine vocational testing, or required time in a treatment program or clinical services prior to participation in VHA Vocational Rehabilitation" (p. 43 and resources needed for successful transition to competitive employment.…”
Section: Vha Vocational Rehabilitationmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, sustained treatment can be viewed as advantageous, while on the other hand, reduced treatment engagement following employment can be indicative of veterans’ improved well-being and reduced need for such services. 1 , 4 , 7 , 15 Thus, the findings of Abraham et al can be considered positive.…”
Section: Introductionmentioning
confidence: 98%